Treatment of Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Very-high-dose phenobarbital was used for refractory status epilepticus in 50 children treated in the Neurology Division, Children's Hospital, University of Southern California School of Medicine, Los Angeles, CA.